Literary Studies and Language Studies in Tamil - Sanmugadas, A. (Faculty of Arts University of Jaffna, 2022)
This paper strives to present a historical view of Tamil studies in Sri Lanka in the context of commercialization of education, the deepening of a market-oriented mindset observed in the wider the society and the crisis in Humanities education. During the Anuradhapura period (65 CE – 993 CE), there were Tamil scholars and Tamil educational institutions active in Anuradhapura. Hisselle Dhammaratana Thera (1963) has written about Tamil teaching in the educational institutions belonging to both the Mahāyāna and Thēravāda sects. Tamil Studies have had a long presence in Sri Lanka, although they were centered around religious institutions in the early periods. When the University College was established in 1921, Tamil began to be taught as a subject at the tertiary level for the first time. At the start, two clergies, namely Professor Swamy Vipulananda, a Hindu sage, and Rev. Fr. C. W. Kinsbury, a Christian priest, contributed to lay a sound foundation for Tamil studies in Sri Lanka. Prof. K. Kanapathipillai, a student of both clergies, later joined them to strengthen Tamil Studies in this country. These three scholars are considered pioneers of Tamil studies in Sri Lanka. The Rev. Dr. Xavier S. Thaninayagam, a renowned Tamil scholar, though specialized in Education, was also at the University of Ceylon. It is noteworthy that the pioneers had both traditional and west-oriented training.
Keywords: Tamiliology; University of jaffna; Tradition; Curriculum; Employment